Efficacy of IV immunoglobulins on depressive symptoms and self-injury: A case report. (13th April 2021) - Silva, A.; Politi, P.; Brondino, N.; Olivola, M.
Abstract : Introduction: Some studies in literature highlight the correlation between immune-mediated inflammatory processes and psychiatric pathologies. However, there are few studies about the efficacy of IV immunoglobulins in psychiatric features (1). (1) ZUNSZAIN, Patricia A.; HEPGUL, Nilay; PARIANTE, Carmine M. Inflammation and depression. In: Behavioral neurobiology of depression and its treatment. Springer, Berlin, Heidelberg, 2012. p. 135-151. Objectives: Case report: a 39 year patient diagnosed with borderline personality disorder and myasthenia was hospitalized for self-injury ideation, acting out and depressive episode treated with acid valproic, aripiprazole, gabapentin; flare-up of myasthenia that needed treatment. Methods: Clinical and test evaluation was performed in three stages: before (t0), immediately after (t1) and 3 weeks after (t2) the administration of the IgEV without other treatment modifications. We have used: - Inventory of Statements About Self-Injury (ISAS) - Barrat Impulsiveness Scale, Version 11 (BIS-11) - Hamilton Anxiety Rating Scale (HAM-A) - Montgomery-Asberg Depression Rating Scale (MADRS) - Alexian Brothers Urge to Selfe-Injure Scale (ABUSI) Results: The patient has a score of 79 at BIS-11. She used to have a huge number of acting aout as we see on ISAS (Fig.1). Figure 1 Figure 2 Conclusions: We observed a reduction in non-suicidal self-injurious ideation, the suspension of acting-out, a complete remission of depressive symptoms with mild persistence of anxious symptoms immediately after the administration of immunoglobulins, and the remission continue until one month after the administration (Fig.2). Disclosure: No significant relationships.